Efficacy of clinical diagnostic criteria for familial hypercholesterolemia genetic testing in Poland. (June 2016) - Mickiewicz, Agnieszka; Chmara, Magdalena; Futema, Marta; Fijalkowski, Marcin; Chlebus, Krzysztof; Galaska, Rafał; Bandurski, Tomasz; Pajkowski, Marcin; Zuk, Monika; Wasag, Bartosz; Limon, Janusz; Rynkiewicz, Andrzej; et al.
Abstract: Background and Aims: Familial hypercholesterolemia (FH), which leads to premature cardiovascular events, still remains underrecognized and undertreated in most countries. Untreated FH individuals aged 20–39 years are at 100-fold higher risk of mortality from coronary heart disease compared to those of a general population. Therefore, special efforts should be implemented to diagnose FH patients at early stages of life. The aim of this study was to evaluate the efficacy of the revised Dutch Lipid Clinic Network (DLCN) criteria proposed by the Polish Lipid Experts Forum to select index FH patients for DNA mutational analysis in Poland. Methods: The study included 193 unrelated adult patients (mean age 48 ± 13 years) with clinical diagnosis of FH based on the revised DLCN score, tested sequentially for mutations in LDLR and APOB genes using bidirectional Sanger sequencing and MLPA techniques. The cut-off points of the clinical FH criteria score were assessed by ROC statistics to identify patients with the highest probability of carrying an FH-causing mutation. Results: The causal heterozygous LDLR or APOB mutation was identified in 41% (80/193) of probands. Adults aged <40 years were more likely to carry an FH-causing mutation compared to subjects aged ≥40 years (65% vs. 33%; p < 0.001). LDL-C thresholds for the molecular diagnosis of FH were 5.79 mmol/l for individuals aged<40 and 6.7 mmol/l for subjects ≥40 years old. The threshold values of the clinical diagnostic score for efficient selection of patients for genetic testing were 5 and 7 points for individuals aged <40 and ≥40 years, respectively. Conclusions: The study validated the efficacy of proposed clinical FH criteria for the disease diagnosis in Poland. The clinical criteria score thresholds for positive FH molecular diagnosis differ depending on age (<40 and ≥40 years). We propose that in the healthcare systems with limited genetic testing resources individuals younger than 40 years, who fulfill the clinical criteria for possible, probable or definite FH should qualify for the FH mutation testing. The index patients aged ≥40 years with clinical diagnosis of probable or definite FH should also qualify for the genetic testing. Highlights: We examined the efficacy of the revised FH clinical criteria for genetic testing. Clinical criteria score thresholds differ depending on age. Adults aged <40 y are more likely to carry an FH-causing mutation than subjects ≥40 y. All subjects with clinical FH aged <40 years should qualify for genetic testing.